Study of vortex shedding around bluff body using air flow test rig - Rafiuddin, Azman (2008)
The Ahmed body represents a simplified car of 3D geometry model that can be used to study the flow characteristic in the wake of vehicles. The main objective of this study is to study the flow pattern around the model by the experimental and simulation method. The model that proposed for present work is 30 o slant angle. The experiment is conducted by using low speed wind tunnel and varied the air velocity, 0.6m/s and 6.0m/s. The time averaged results of smoke flow pattern at the curvature part is discussed. Major finding shows that the formation of small vortex is decay in time and distance as the flow travelling further. Furthermore, although overall of the smoke flow pattern results showed good agreement with previously published work, the flows structure behind the model was found to be somewhat inconsistency in a separated region over the slant and the recirculation flows behind the model. The observation indicates that the formation of small vortices over the slant is not clear apparent instead of the flows is mixing with recirculation vortices. In addition, the flow pattern of the recirculation vortices behind the model showed very similar with the previous works, indicating two vortices is formed, emphasizing in findings.